Integration of Augmented Reality in Physics E-Module: Heat and Heat Transfer Study through Ulos Making for Enhancing Analytical Thinking - Nasution, Eni Sumanti; Kasmawati; Sarpin (International Journal of Natural Science Studies and Development (IJOSS), 2025)
This research developed an Augmented Reality (AR)-based physics e-module that integrates heat and heat transfer concepts through the local wisdom of Ulos making to enhance students' analytical thinking skills. The study employed Research and Development (R&D) methodology using the ADDIE model. The subjects were 30 seventh-grade students from SMP Negeri 5 Padangsidimpuan. Data collection instruments included expert validation questionnaires, practicality questionnaires from teachers and students, pre-test and post-test for analytical thinking, observation sheets, and interviews. Data analysis used descriptive statistics and paired sample t-test. The results showed that the AR e-module was highly valid with an average validation score of 88.5% from material, media, and pedagogy experts. The practicality level was categorized as very practical according to teachers (86%) and students (88%). The effectiveness test demonstrated significant improvement in students' analytical thinking skills with an N-Gain of 0.58 (moderate category) and significant t-test results (p < 0.001). The integration of Ulos cultural context with AR technology successfully created meaningful learning experiences and increased student motivation by 94%. This research supports SDG 4 (Quality Education) by providing innovative technology-based learning methods that preserve local cultural wisdom.